Karawa Media (Karambol Aksara Jawa) Assisted by Reading Cards to Improve Reading Skills in Nglegena Javanese Script - Kailifa Zakia Azzahra; Sukardi (Jurnal Ilmiah Sekolah Dasar, 2023)
The content of Javanese lessons still needs to be more exciting, plus the teacher's method of delivering the material is using the lecture method. This has an impact on student learning outcomes. This research aims to create Karawa media (Karambol Aksara Jawa) for the content of Javanese language learning for class III elementary school students to improve their reading skills in the Javanese Nglegena script. This research is development research using the ADDIE model. The subjects of this research were 32 class III students, class III teachers, and a team of experts (media and materials). Data collection methods use observation, tests, questionnaires and interviews. Data analysis techniques use quantitative descriptive, qualitative descriptive and inferential statistics. The research results showed that the material expert trial, media expert trial, small group trial and class teacher trial were feasible. The results of the effectiveness test using the paired t-test show that the results of the pre-test and post-test both have an increase, so it can be concluded that there is a significant difference between the results of the large and small groups. Therefore, Karawa media using Javanese Nglegena script material is very effective, efficient, and suitable for use in the educational process because it can improve the reading skills of Javanese Nglegena script for third-grade elementary school students. This research implies that it can help teachers deliver Javanese Nglegena script material for Javanese language learning content for Class III Elementary School.